Appendix from No place like home? A test of the natal habitat-biased dispersal hypothesis in Scandinavian wolves. - Ana Sanz Perez; Andrés Ordiz; Håkan Sand; Jon E. Swenson; Petter Wabakken; Camilla Wikenros; Barbara Zimmermann; Mikael Åkesson; Cyril Milleret (2018)
Supplementary information about the study area, definition of habitat availability and definition of habitat similarity